2021
DOI: 10.1590/1980-220x-reeusp-2020-0499
|View full text |Cite
|
Sign up to set email alerts
|

Nursing diagnoses, results, and interventions in the care for Covid-19 patients in critical condition

Abstract: Objective: To develop and validate a terminological subset of the International Classification for Nursing Practice for COVID-19 patients in critical care. Method: This is a methodological study, which followed the guidelines of the Brazilian method, using the Basic Human Needs as a theoretical model. Content validation was performed by 25 specialist nurses using the Delphi technique. Results: A total of 73 diagnoses and their respective nursing results were prepared. Of these, 62 statements had a Content Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Two studies using clinical data showed the value of using standardised terminologies, such as Omaha and NANDA-I, when describing nursing care of COVID-19 patients (Ardic & Turan, 2021;Asghari et al, 2021). Moreover, terms relevant to the context of COVID-19-hospitalised patients have been identified from the literature (Barros et al 2020;de Souza et al 2020;Menezes et al 2021;Santos et al, 2021), official documents (Aguña et al 2021a(Aguña et al , 2021bAraújo et al 2021) and care plans (Swanson et al 2021) and mapped to the standardised nursing languages NANDA-I, Nursing Outcomes Classification (NOC), NIC and the 2019 version of ICNP. The results indicate that terms in ICNP represent the specific context of nursing practice for COVID-19 patients ( de Souza et al, 2020;Santos et al, 2021).…”
Section: Icnp As a Reference Set In Systematized Nomenclature Of Medi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies using clinical data showed the value of using standardised terminologies, such as Omaha and NANDA-I, when describing nursing care of COVID-19 patients (Ardic & Turan, 2021;Asghari et al, 2021). Moreover, terms relevant to the context of COVID-19-hospitalised patients have been identified from the literature (Barros et al 2020;de Souza et al 2020;Menezes et al 2021;Santos et al, 2021), official documents (Aguña et al 2021a(Aguña et al , 2021bAraújo et al 2021) and care plans (Swanson et al 2021) and mapped to the standardised nursing languages NANDA-I, Nursing Outcomes Classification (NOC), NIC and the 2019 version of ICNP. The results indicate that terms in ICNP represent the specific context of nursing practice for COVID-19 patients ( de Souza et al, 2020;Santos et al, 2021).…”
Section: Icnp As a Reference Set In Systematized Nomenclature Of Medi...mentioning
confidence: 99%
“…2020; Menezes et al. 2021; Santos et al., 2021), official documents (Aguña et al. 2021a, 2021b; Araújo et al.…”
Section: Introductionmentioning
confidence: 99%
“…The literature points out that the elaboration of a terminological subset establishes a systematic practice, since the affected needs of individuals can be addressed, assessed and encouraged to resolve (19)(20) . Thus, the development of a subset for people with diabetic foot ulcers in PHC favors nurses' decision-making at the first individual and collective point of contact, offering promotion, prevention, treatment, rehabilitation and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The ICNP ® has shown promise in expanding the clinical judgment of nurses and by inserting new elements originated from practice in several areas, including Covid-19. Thus, it is shown as a powerful technology for current aspects and, once again contributes by documenting nursing care standards [30][31] .…”
Section: /16mentioning
confidence: 99%